The medieval heart - Webb, Heather, 1976- (New Haven [Conn.] : Yale University Press, 2010)
"Heather Webb studies medieval notions of the heart to explore the "lost circulations" of an era when individual lives and bodies were defined by their extensions into the world rather than as self-perpetuating, self-limited entities. Drawing from the works of Dante, Catherine of Siena, Boccaccio, Aquinas, and Cavalcanti and other literary, philosophic, and scientific texts, she reveals medieval answers to such fundamental questions as: Where is life located? What does it consist of? Where does it begin? And how does it end? Against the modern idea of the isolated self, the medieval heart provides a model for rethinking the body's relationship to the world it inhabits."--Jacket
The sovereign heart -- The porous heart -- The engendering heart -- The animate heart.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: Civilization, Medieval; Human body (Philosophy) -- History; Heart -- Symbolic aspects -- History; Medical literature -- History -- To 1500.; Heart in literature; Mind and body -- History; Heart; Medicine, Medieval; Heart; History, Medieval; Human Body; Literature, Medieval -- history; Mind-Body Relations, Metaphysical; Symbolism; Civilisation médiévale.; Corps humain (Philosophie) -- Histoire; Cœur dans la littérature.; Cœur; Médecine médiévale.; HISTORY -- Medieval; MEDICAL -- History; Medicine, Medieval; Heart; Civilization, Medieval; Heart in literature; Heart -- Symbolic aspects; Human body (Philosophy); Medical literature; Mind and body; Mittelalter; Literatur; Herz; Körper; Kulturhistoria -- medeltiden; Hjärta i litteraturen -- medeltiden; Människokroppen -- medeltiden; Kropp och själ -- historia -- medeltiden; Hjärta -- idéhistoriska aspekter -- medeltiden; Herz (Motiv); Körper (Motiv); To 1500; History